Differential contributions of two domains of NAI2 to the formation of the endoplasmic reticulum body - Choi, Yun Ju; Geem, Kyoung Rok; Kim, Jitae; Lee, Dong Wook (Frontiers in Plant Science, 2023)
The endoplasmic reticulum (ER) serves essential functions in eukaryotic cells, including protein folding, transport of secretory proteins, and lipid synthesis. The ER is a highly dynamic organelle that generates various types of compartments. Among them, the ER body is specifically present in plants in the Brassicaceae family and plays a crucial role in chemical defense against pathogens. The NAI2 protein is essential for ER body formation, and its ectopic overexpression is sufficient to induce ER body formation even in the leaves of Nicotiana benthamiana, where the ER body does not naturally exist. Despite the significance of NAI2 in ER body formation, the mechanism whereby NAI2 mediates ER body formation is not fully clear. This study aimed to investigate how two domains of Arabidopsis NAI2, the Glu-Phe-Glu (EFE) domain (ED) and the NAI2 domain (ND), contribute to ER body formation in N. benthamiana leaves. Using co-immunoprecipitation and bimolecular fluorescence complementation assays, we found that the ND is critical for homomeric interaction of NAI2 and ER body formation. Moreover, deletion of ED induced the formation of enlarged ER bodies, suggesting that ED plays a regulatory role during ER body formation. Our results indicate that the two domains of NAI2 cooperate to induce ER body formation in a balanced manner.